2019
DOI: 10.1093/nar/gkz1075
|View full text |Cite
|
Sign up to set email alerts
|

The histone variant H2A.Z in yeast is almost exclusively incorporated into the +1 nucleosome in the direction of transcription

Abstract: Transcription start sites (TSS) in eukaryotes are characterized by a nucleosome-depleted region (NDR), which appears to be flanked upstream and downstream by strongly positioned nucleosomes incorporating the histone variant H2A.Z. H2A.Z associates with both active and repressed TSS and is important for priming genes for rapid transcriptional activation. However, the determinants of H2A.Z occupancy at specific nucleosomes and its relationship to transcription initiation remain unclear. To further elucidate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 72 publications
5
36
0
Order By: Relevance
“…While it is possible that this occurred through disruption of targeted H2A.Z eviction, no mechanism for ANP32E targeting has been described. On the contrary, targeted H2A.Z installation is known to occur specifically at the NDRs and at the +1 nucleosome position 11 , 36 , 37 , 58 . Therefore, rather than invoking H2A.Z eviction, we favor a simpler explanation for how H2A.Z accumulated at the −1 position.…”
Section: Discussionmentioning
confidence: 99%
“…While it is possible that this occurred through disruption of targeted H2A.Z eviction, no mechanism for ANP32E targeting has been described. On the contrary, targeted H2A.Z installation is known to occur specifically at the NDRs and at the +1 nucleosome position 11 , 36 , 37 , 58 . Therefore, rather than invoking H2A.Z eviction, we favor a simpler explanation for how H2A.Z accumulated at the −1 position.…”
Section: Discussionmentioning
confidence: 99%
“…S2G, Left). Moreover, the distance of pausing site shift in Ino80p-KD showed no significant correlation with H2A.Z Htz1 enrichment in the +1 nucleosome, which is calculated from an existing MNase-ChIP-seq ( 38 ) (fig. S2G, Right).…”
Section: Resultsmentioning
confidence: 96%
“…In this regard, a good closing example of this is provided by two very recent seemingly contradictory reports which have come up at the time of writing this review. In the first, it is indicated that in yeast, H2A.Z is almost exclusively incorporated into the +1 nucleosome in the direction of transcription, suggesting that H2A.Z has a causative role in the transcription initiation process at this location [99]. In the second, using H2A.Z KO post-mitotic muscle cells, it is shown that this histone variant is neither required to maintain nor to activate transcription which would be in line with the concept that H2A.Z is not a direct player but rather a marker of transcription [11,100].…”
Section: Discussionmentioning
confidence: 99%